Perimyocarditis versus Myocardial Infarction with ST Segment Elevation-MINOCA as a Starting Point - Stojanovic, Milovan; Ilic, Bojan; Deljanin-Ilic, Marina; Ilic, Stevan; Petrovic, Dejan; Stojanovic, Sanja (Indian Journal of Pharmacy Practice)
Myocardial Infarction with Non-obstructive Coronary Arteries (MINOCA) represents a relatively new entity in cardiovascular medicine. According to the fourth universal definition of myocardial infarction MINOCA is characterised by typical chest pain with the appearance of ST segment elevation on the electrocardiogram (ECG) but without any significant stenotic lesions on coronary angiography. MINOCA is a working diagnose as there are several potential lethal diseases like pulmonary embolism, aortic dissection, perymiocarditis, etc., that can have similar clinical presentation. This is why MINOCA requires further investigations and the use of contemporary diagnostic methods in order to make a definite diagnosis. The most commonly used non-invasive diagnostic procedures are transthoracic and transoesophageal echocardiography, computed tomography and cardiac magnetic resonance imaging. Sometimes MINOCA is caused by prolonged coronary arteries spasm – vasospastic angina. This condition requires further instigations such administration of intracoronary acetylcholine. This case report is an example taken from everyday clinical practice. A young man had a typical chest pain with ST segment elevation on ECG and high troponin levels in the blood. After echocardiography and invasive diagnostic procedure, we came to the conclusion that patient suffered from primyocaridtis.
Keywords: Myocardial infarction; MINOCA; Perimyocarditis; ST segment elevation; Coronary angiography; Chest pain.